Use of complementary medicine and its association with SARS-CoV-2 vaccination during the COVID-19 pandemic: a longitudinal cohort study (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: Patients are increasingly using and requesting complementary medicine therapies, especially during the COVID-19 pandemic. However, it remains unclear whether they use them in conjunction with conventional medicine or to replace vaccination or other approaches and whether they discuss them with their physicians as part of shared decision-making. This study aimed to evaluate the use and initiation of complementary medicine during the COVID-19 pandemic, focusing on the association between complementary medicine use and COVID-19 vaccination status.METHODS: This study is a part of the longitudinal cohort of the CoviCare program, which follows all outpatients tested for COVID-19 at the Geneva University Hospitals. Outpatients tested for COVID-19 were contacted 12 months after their positive or negative test between April and December 2021. Participants were asked about their vaccination status and if they had used complementary medicine in the past 12 months. Complementary medicine use was defined based on a specific list of therapies from which participants could choose the options they had used. Logistic regression models adjusting for age, sex, education, profession, severe acute respiratory system coronavirus 2 (SARS-CoV-2) infection, and pre-existing conditions were used to evaluate the association between being unvaccinated and complementary medicine use. SARS-CoV-2 infection status was evaluated for effect modification in the association between being unvaccinated and complementary medicine use.RESULTS: This study enrolled 12,246 individuals (participation proportion = 17.7%). Their mean age was 42.8 years, 59.4% were women, and 63.7% used complementary medicine. Complementary medicine use was higher in women, the middle-aged, and those with a higher education level, a SARS-CoV-2 infection, or pre-existing comorbidities. A third of cases initiated complementary medicine therapies as prevention against COVID-19. Being unvaccinated was associated with complementary medicine use (adjusted odds ratio [aOR] 1.22 [1.09–1.37]), and more specifically when these therapies were used for COVID-19 prevention (aOR 1.61 [1.22–2.12]). Being unvaccinated was associated with the use of zinc (aOR 2.25 [1.98–2.55]), vitamin D (aOR 1.45 [1.30–1.62]), and vitamin C (aOR 1.59 [1.42–1.78]), and more specifically when these therapies were used for COVID-19 prevention. Only 4% of participants discussed using complementary medicine with their primary care physicians.CONCLUSION: While complementary medicine is increasingly used, it is rarely discussed with primary care physicians. Complementary medicine use, especially for COVID-19 prevention, is associated with COVID-19 vaccination status. Communication between physicians, patients, and complementary medicine therapists is encouraged to facilitate a truly holistic approach to making a shared decision based on the best available information.